Overlapping anti-NMDAR encephalitis and multiple sclerosis: A case report and literature review - Liu, Pan; Yan, Hui; Li, Haizhe; Zhang, Chunhua; Li, Yanfang (Frontiers in Immunology, 2023)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune-meditate disease characterized by complicated neuropsychiatric symptoms and the detection of cerebrospinal fluid (CSF) antibodies against the GluN1 subunit of the NMDAR. With the proposed clinical method, more anti-NMDAR encephalitis patients have been discovered since its first report. However， anti-NMDAR encephalitis overlap with multiple sclerosis (MS) is rare. Herein, we reported a male patient with anti-NMDAR encephalitis developed MS in mainland China. Furthermore, we summarized the characteristics of patients who diagnosed with overlapping MS and anti-NMDAR encephalitis in previous studies. Additionally, we pioneered the use of mycophenolate mofetil in immunosuppressive therapy, providing a novel therapeutic alternative for overlapping anti-NMDAR encephalitis and MS.